Preparation of silver sulphide (Ag2S) thin films by chemical bath deposition for photocatalytic application - Nedal A. Hussain; Lamyaa A. Latif; Haidar J. Mohamad (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Semiconductor silver sulphide (Ag2S) thin films were grown on the glass substrate by chemical bath deposition (CBD). Five films deposited at the room temperature in a bath containing an aqueous solution of silver sulphide. The chemically synthesized Ag2S films are annealed at 573K for one hour for the second sample, and two hours for the third sample. The fourth sample exposed to microwave irradiation for one hour, and two hours for the fifth sample. Surface morphology, photocatalytic, optical and structural properties of all Ag2S samples investigated. The optical parameters such as transmittance, absorbance, absorption coefficient and energy bandgap of the films with thermal annealing and expose microwave irradiation presented. Optical measurement shows high absorbance in the ultraviolet-visible (UV-Vis) region. The difference in bandgap values of Ag2S samples was located to be in the range of (1.5-2.05) eV. X-ray diffraction (XRD) measurements reflect the existence of polycrystalline, and the scanning electron microscopy images showed that the morphologies of Ag2S thin films have various microspheres. The summary of the samples in is in the annealing Ag2S thin film which exhibits the best photocatalytic application.